2023
DOI: 10.3390/su15021436
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Outdoor Physical Activities for People with Disabilities, including the Risks for Psychophysical Well-Being

Abstract: The restrictions and social distancing measures due to the COVID-19 pandemic have created many obstacles in the practice of outdoor physical activity (OPA) throughout the world, particularly for the most vulnerable people, such as those with disabilities. The aim of this study was to explore the impact of pandemic-related limitations on the OPA of an Italian cohort of people with disabilities practicing sports. A retrospective observational study was conducted using an online survey. The questionnaire was dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Wheelchair basketball (WB) is an increasingly popular sport. Over the last decade, Paralympic sports, particularly WB, have steadily gained interest [1,2]. Born in the USA at the end of the 40s as a rehabilitation activity for veterans of the Second World War [3], WB today represents an excellent opportunity for physical activity, rehabilitation, and integration for people with disabilities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Wheelchair basketball (WB) is an increasingly popular sport. Over the last decade, Paralympic sports, particularly WB, have steadily gained interest [1,2]. Born in the USA at the end of the 40s as a rehabilitation activity for veterans of the Second World War [3], WB today represents an excellent opportunity for physical activity, rehabilitation, and integration for people with disabilities [4].…”
Section: Introductionmentioning
confidence: 99%
“…The individual serves as the primary nexus in the chain of a sustainable economy, society, and environment [5]. Research indicates key principles for sustainable physical activity, including setting realistic expectations, being cognizant of desired physical, mental, and emotional states, establishing attainable goals, objectively monitoring progress, revising the plan if goals are not met, and integrating exercise as an integral part of lifestyle rather than as a mere ancillary need [6][7][8][9]. Bandura (1977) introduced the concept of self-efficacy as part of 'cognitive behavioral modification' [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these historic steps forward in political and cultural terms, the way to guarantee access to sports for people with disabilities is still very long, and the recent COVID-19 pandemic has shown that many of the limitations make this road tortuous. Access to sports facilities and availability of competent personnel are still limited for people with physical, sensory and cognitive impairments, and the economic resources dedicated to this purposes are not sufficient in normal conditions and even more so in emergency ones [5].…”
mentioning
confidence: 99%